Extra-Judicial Killings in Papua, Indonesia Reflections on Violation and State Authoritarianism Toward Papuans - Saadah, Aliyah Almas (PCD Journal, 2022)
This article aims to elaborate on and explore extrajudicial killings, i.e.,the human rights violations conducted by Indonesian state security forces in Papua. Such unlawful executions are tightly intertwined with the history of torture and forced disappearance during the lengthy conflict in Papua and West Papua. Despite claiming numerous victims, security officials have never been held fully accountable for extrajudicial killings due to their “legal impunity” and the lack of political will to bring perpetrators to trial. Importantly, this article shows that the reported killings are only the tip of the iceberg, as human rights experts and scholars believe there are many more profound and severe violations of Papuans’ rights. Journalists’ limited access to documents, as well as general non-disclosure, has created speculation that numerous human rights violations have occurred but gone unreported. First, we urge the government to recognise extrajudicial killings as gross and severehuman rights violations, as defined by international law. Second, the government must comprehensively review police, military, or other security officials’ fieldwork and use of firearms and physical force when arresting suspects.